Implementing the Guided Inquiry Approach in IPAS Learning at the Elementary Level: A Literature Review (2021–2026) - Na'im Mushlihurrohman; Tutik Wijayanti; Decky Avrilianda; Agung Tri Prasetya (International Journal of Research in Education, 2026)
The Guided Inquiry approach provides students with opportunities to actively engage in the learning process through investigation, data collection, and drawing conclusions. This approach directly fosters critical thinking skills, including interpretation, analysis, evaluation, and inference. This study aims to analyze the effectiveness of the Guided Inquiry model in teaching Natural and Social Sciences (IPAS) at the elementary school level. The research method employed is a Systematic Literature Review (SLR) by analyzing 796 articles from Scopus and Google Scholar databases published between 2021 and 2026. Based on the literature review, the findings indicate that this model significantly improves students’ critical thinking skills, conceptual understanding, and learning motivation. The results show that these improvements occur due to the shift in students’ roles from passive recipients to active discoverers through systematic learning stages. Furthermore, the integration of digital technologies such as video media, PhET Simulations, and Google Sites enhances learning outcomes by making abstract concepts more concrete. Therefore, the Guided Inquiry approach can serve as a strategic solution in developing science learning aligned with the demands of 21st-century education in elementary schools.